Introduction To Fractional Calculus Amna Al - Amri Project October 2010
Introduction To Fractional Calculus Amna Al - Amri Project October 2010
Introduction To Fractional Calculus Amna Al - Amri Project October 2010
A Project
Submitted to the University of Nizwa in Partial Fulfillment of the
Requirements for the Degree of Bachelor of Education in Mathematics
By
Supervised by
Professor Dr. Ahmed S. El-Karamany
2010
Supervisor Certification
Signature
Signature
Committee Certification
ABDULSALAM YOUNIS AL-AMRY in its contents and what it connected with it,
and that our opinion it meets the standard of project for degree bachelor of Education
in Mathematics.
1) Signature
2) Signature
3) Signature
Name: Dr. Mahmood Khalid Jasim
Associate Professor
Member Date: 27/5/2010
Approved by:
Professor Dr. Ahmed S. El-Karamany
Head of Department of Mathematical and Physical Sciences.
Date: 27/5/2010
Abstract
Abstract
This work is devoted to explore Fractional Calculus which has been used
successfully to modify many existing models of Physical processes.
The Work consists of 5 chapters. In chapter 1; the introduction, some historical notes
and an approach to fractional calculus using generalization of Cauchy formula for
n –folde integral. Laplace transform of the convolution and its properties are given.
Integrals and derivatives of fractional order are defined in chapter 2. In this Chapter
integrals and derivatives of fractional order of power and exponential functions are
calculated. Semi-integrals and semi-derivatives of power function, exponential function,
sine and cosine functions are given in chapter 3. In chapter 4 some illustrating solved
problems are given. The Tautochrone problem is discussed in chapter 5 as an application
of semi-derivatives in solving Abel’s integral equation. A list of references is given at the
end of this project.
i
ACKNOWLEDGEMENT
of Arts & Sciences and to all staff members for their assistance and
and help.
Contents
Chapter 1
1.1 Introduction……………………………………………………………………. …..1
1.2 Birth of Fractional Calculus ………………………………………………………..2
1.3 Fractional Calculus as Generalization of Integer Order Calculus…………....... 3
Chapter 2
Fractional integrals and derivatives……………………………………………………6
Chapter 3
Semi- integrals and Semi-derivatives………………………………………………….12
Chapter 4
Semi- Integrals and Semi-Derivatives of Some Algebraic Functions ……………….16
Chapter 5: Application
The Tautochrone Curve ……………………………………………………………… 19
References …………………………………………………………………………… 22
i
1
Chapter 1
Introduction
1.1 Introduction
Fractional calculus is three centuries old as the conventional calculus, but not very
popular among science and/or engineering community. The beauty of this subject
is that fractional derivatives (and integrals) are not a local (or point) property (or
quantity). Thereby this considers the history and non-local distributed effects. In
other words, perhaps this subject translates the reality of nature better! Therefore
to make this subject available as popular subject to science and engineering community,
it adds another dimension to understand or describe basic nature in a better
way. Perhaps fractional calculus is what nature understands, and to talk with nature
in this language is therefore efficient. For the past three centuries, this subject was with
mathematicians, and only in last few years, this was pulled to several (applied) fields
of engineering , science and economics. However, recent attempt is on to have
the definition of fractional derivative as local operator specifically to fractal science
theory. Next decade will see several applications based on this 300 years (old) new
subject, which can be thought of as superset of fractional differintegral calculus, the
conventional integer order calculus being a part of it. Differintegration is an operator
doing differentiation and sometimes integrations, in a general sense. In this project,
fractional order is limited to only real numbers; the complex order differentigrations
are not touched. Also the applications and discussions are limited to fixed fractional
order differintegrals, and the variable order of differintegation is kept as a future
research subject. Perhaps the fractional calculus will be the calculus of twenty-first
century. In this project, attempt is made to make this topic application oriented for
regular science and engineering applications. Therefore, rigorous mathematics is
kept minimal. In this introductory chapter.
1.2 Birth of Fractional Calculus
In a letter dated 30th September 1695, L’Hopital wrote to Leibniz asking him a
particular notation that he had used in his publication for the nth derivative of a
function
2
D nf
Dx n
i.e., what would the result be if n = 1/2. Leibniz’s response “ an apparent paradox
from which one day useful consequences will be drawn.” (Debnath 2004) In these
words, fractional calculus was born. Studies over the intervening 300 years have proved
at least half right. It is clear that within the twentieth century especially numerous
applications have been found. However, these applications and mathematical background
surrounding fractional calculus are far from paradoxical. While the physical meaning is
difficult to grasp, the definitions are no more rigorous than integer order counterpart.
∫
L{ f (t )} = e − st f (t )dt = F ( s ) (1.1)
0
∫ ∫
(f ∗ g )(t ) = f (t − x ) g (x )dx = f (t − y ) g ( y )dy (1.2)
0 0
∫ ∫
(f ∗ g )(t ) = f (t − x ) g (x )dx = ( g ∗ f )(t ) = g (t − x )f (x )dx (1.3)
0 0
3
Proof: From the definitions of Laplace transform and the convolution we get
∞ t ∞ t
∫ ∫ ∫ ∫e
− st − st
L{ f ∗ g} = e ( f ( y ) g (t − y )dy ) dt = f ( y ) g (t − y ) dydt (1.6)
0 0 0 0
The region of integration is a simple vertically region in the tOy plane where Oy is the
vertical axis and Ot is the horizontal axis.
It is the triangle in the first coordinate quarter whose base in the infinity and whose sides
R h = {(t , y ) : y ≤ t < ∞ 0 ≤ y < ∞} and the integral (1.6) takes the form
∞ t ∞ ∞
∫ ∫e ∫ ∫e
− st − st
L{ f ∗ g} = f ( y ) g (t − y )dydt = f ( y ) g (t − y ) dtdy
0 0 0 y
∞ ∞
∫ f ( y)(∫ e
− st
= g (t − y )dt )dy
0 y
∫ ∫e ∫ ∫e
− st − s ( x+ y )
L{ f ∗ g} == f ( y )( g (t − y )dt )dy = f ( y )( g ( x)dx) dy
y =0 t= y y =0 x =0
∞ ∞
∫ ∫
− sy
=( e f ( y )dy )( e − sx g ( x)dx) = F ( s )G ( s )
0 0
∫
−1
L {F (s )G (s )} = (f ∗ g ) = f (t − x ) g (x )dx (1.7)
0
4
Below is the Laplace transforms and inverse Laplace transforms of some functions that
play an essential role in the generalization we are going to present
The Laplace transform and the inverse Laplace transform of some functions:
Laplace Transform The Inverse Laplace Transform
1 (n − 1)! 1 t n −1
L {t n −1} = −1
L { n}=
sn s Γ (n )
2 t t
F (s ) F (s )
∫ ∫
−1
L { f (x )dx } = L { } = f (x )dx
s s
0 0
3 t t t t
F (s ) F (s )
∫∫ ∫∫ f (x )dxdx
−1
L { f (x )dxdx } = 2 L { 2 }=
00
s s 00
4 t t t t t t
F (s ) F (s )
∫∫ … ∫ ∫∫… ∫
−1
L{ f (x )dxdx …dx } = n L { n }= f (x ) dxdx …dx
0o 0
s s 00 0 n
n n
−n
=D f (t )
Where
∞ ∞
∫ ∫
2
p −1 − x
Γ( p ) = x e dx = 2 x 2 p −1e − x dx (1.8)
0 0
1 t n −1
Using the convolution theorem with G (s ) = n , g (t ) = we obtain
s Γ(n )
t n −1
t t
F (s ) 1 1
∫ ∫
−1
L { n } = (f ∗ )(t ) = f (x )(t − x ) n −1dx = x n −1f (t − x )dx
s Γ ( n ) Γ ( n )
0
Γ ( n )
0
Here we have used that if two continuous functions have the same Laplace transform they
are identical (Learch Theorem). This means that we restrict our derivation to include only
continuous functions
5
Equation (1.8) is called the Cauchy formula for n-folder integral where n ∈ .
Riemann and Liouville generalized Cauchy formula to any fractional number ν and got
the Riemann-Liouville fractional integral
t
1
∫
−ν
D f (t ) = (t − x )ν −1 f (x )dx ν∈ +
,t > 0 (1.9)
Γ (ν ) 0
When 0 < ν < 1 we have an improper integral of second type which is convergent by
the p- test since 1 −ν < 1 . The integral is also convergent for ν = 1 . Therefore the
conditions for the existence of integral (1.9) is that f (t ) should be Riemann integrable
on (0, ∞) .
The Riemann – Liouville fractional derivative is defined by
D ν f (t ) = D m ⎡⎣ D − ( m −ν )f (t ) ⎤⎦
t
dm dm 1
dt Γ(m −ν ) ∫0
= m D − ( m −ν ) f (t ) = m [ (t − x )m −ν −1 f (x )dx ]
dt
m −1 <ν ≤ m , m ∈
We shall not discuss here other definitions of fractional derivatives where the function
f (t ) is required to be Lebesgue integrable and absolutely continuous (Samko et all
1993).
Chapter 2
Fractional integrals and derivatives
Definition (1): Let ν > 0 and let f be continuous on (0, ∞) and integrable on any
∫ f (t ) dt
−1
J f (t ) = D f (t ) = f (t ) , J f (t ) = D f (t ) =
0 0 1
(2.1b)
0
t t
C C
∫ ∫
= 1 (t − x )ν −1 f (x )dx ± 2 (t − x )ν −1 g (x )dx = C 1D −ν f (t ) ± C 2 D −ν g (t )
Γ (ν ) Γ (ν )
0 0
(t ν +λ ) t ν +λ t ν +λ Γ (λ + 1)
1
∫
−ν λ
D (t ) = (1 − u )ν −1u λ du = B (ν , λ + 1) = (2.4)
Γ (ν ) 0
Γ (ν ) Γ (ν + λ + 1)
7
Ct ν +λ Γ (λ + 1) C tν
D −ν (C ) = lim[D −ν (Ct λ )] = lim = (2.5)
λ →0 λ →0 Γ (ν + λ + 1) Γ (ν + 1)
As special case we get the fraction integral of f (t ) = 1
tν
D −ν (1) = ν >0 (2.6)
Γ (ν + 1)
Example (3): The fractional integral of the exponential function
f (t ) = e αt , α ≠ 0.
e αt
t t
1
∫ ∫
−ν αt
D (e ) = x ν −1e α (t −x )dx = x ν −1e −α x dx
Γ (ν ) 0
Γ (ν ) 0
∫
γ (ν , x ) = t ν −1e −t dt (2.8)
0
α −ν e αt γ (ν ,αt )
E t (ν , α ) = (2.9)
Γ (ν )
Definition (2):: The fractional derivative of f (t ) of order µ > 0 (if exists) can be
D µ f (t ) = D m ⎡⎣ D − ( m − µ ) f (t ) ⎤⎦ (2.10)
f (t ) = t λ , λ > −1
8
⎡ Γ (λ + 1) t λ − µ + m ⎤
D µ (t λ ) = D m [D − ( m − µ ) (t λ )] = D m ⎢ ⎥ (2.11)
⎣ Γ (1 + m + λ − µ ) ⎦
Since m is integer, Eq. (2.11) yields
t −µ
D µ (1) = , ( µ is a noninteger ) (2.16)
Γ (1 − µ )
Before proving some properties of the fractional derivatives we introduce the Leibniz
rule for the fractional derivative of product of two functions.
Leibniz rule: For integer n the Leibniz rule for the product of two n time’s
differentiable functions can be written in the form
k =n
Γ(n + 1)
D n [ f (t ) g (t )] = ∑ Γ(k + 1)Γ(n + 1 − k ) Dn−k f (t ) Dk g (t )
k =0
n(n − 1) n−2
( ) ( )
= D n f (t ) g (t ) + n D n−1 f (t ) Dg (t ) +
2
( )
D f (t ) D 2 g (t ) + (
+ f (t ) D n g (t ) )
k =n
Γ( n + 1)
= ∑ Γ(k + 1)Γ(n + 1 − k ) Dk f (t ) Dn−k g (t ) (2.17)
k =0
The analogy between the two expressions (2.14) and (2.15) suggests to generalize
(2.17) for the fractional derivative of order ν > 0 as follows
9
∞
Γ(ν + 1)
Dν [ f (t ) g (t )] = ∑ Γ(k + 1)Γ(ν + 1 − k ) Dν −k f (t ) D k g (t )
k =0
( ) (
= D f (t ) g (t ) + ν Dν −1 f (t ) Dg (t ) +
ν
) (
+ f (t ) Dν g (t ) +)
∞
Γ(ν + 1)
= ∑ Γ(k + 1)Γ(ν + 1 − k ) Dk f (t ) Dν −k g (t ) (2.18)
k =0
Since ν is not integer the upper limit of the sum in (2.18) is infinite.
Now, we are able to prove the following properties of the fractional derivative.
Property (1): Let g (t ) = C is the constant function, then
g (t ) = C into (2.18):
∞
Γ(ν + 1)
ν
D [ f (t )C ] = ∑ Γ(k + 1)Γ(ν + 1 − k ) Dν −k f (t ) Dk C = ( Dν f (t ) ) C = C ( Dν f (t ) )
k =0
Property (2):
(
Dν [ f (t ) + h(t )] = Dν f (t ) + Dν h(t ) ) ( ) (2.20)
∞
Γ(ν + 1)
Dν [t 0 ( f (t ) + h(t ) )] = ∑ Γ(k + 1)Γ(ν + 1 − k ) Dν −k f (t ) Dk t 0
k =0
∞
Γ(ν + 1)
+ ∑ Γ(k + 1)Γ(ν + 1 − k ) Dν −k h(t ) Dk t 0 = ( Dν f (t ) ) + ( Dν g (t ) )
k =0
Combining properties (1) and (2) we obtain the following linearity property of the
fractional derivative
( )
D ν [C 1f (t ) + C 2 h (t )] = C 1 D ν f (t ) + C 2 D ν h (t ) ( ) (2.21)
(i) D −ν ( D − µ f (t )) = D − (ν + µ ) f (t ) (2.25a)
(ii) D − µ ( D −ν f (t )) = D −ν ( D − µ f (t )) (2.25b)
For f ∈C , 0 < ν < 1 and 0 < µ < 1
10
If we consider the vertical axis is O ξ then the region of integration in the preceding
double integral is the triangle OPM in Fig. (1) and it is a simple vertical region
R v = {( x, ξ ) : 0 ≤ x ≤ t , 0 ≤ ξ ≤ x}
Changing the region of integration from simple vertical to simple horizontal we get
t 1 t
1 B ( µ ,ν )
=
Γ(ν )Γ( µ ) ∫∫
( u µ −1 (1 − u )ν −1du )(t − ξ )ν + µ −1 f (ξ )d ξ =
Γ(ν )Γ( µ ) ∫
(t − ξ )ν + µ −1 f (ξ )d ξ
0 0 0
t
1
=
Γ(ν + µ ) ∫
(t − ξ )ν + µ −1 f (ξ )d ξ = D − (ν + µ ) f (t ) (2.30)
0
Applying D − µ we get
t
1
∫
−µ
D (h(t )) = (t − x) µ −1 h( x)dx
Γ( µ )
0
t x
1
∫ ∫
−µ −ν
D (D f (t )) = (t − x) µ −1 ( ( x − ξ )ν −1 f (ξ ) dξ )dx
Γ(ν )Γ( µ )
0 0
t x
1
∫∫ (t − x)
µ −1
= ( x − ξ )ν −1 f (ξ )dξ dx (2.31)
Γ(ν )Γ( µ )
00
Since the region of integration is the same region shown in Fig. (1) we get upon
reversing the order of integration
t t
1
∫∫ (t − x)
−µ −ν µ −1
D (D f (t )) = ( x − ξ )ν −1 f (ξ )dxd ξ
Γ(ν )Γ( µ )
0ξ
Since B ( µ ,ν ) = B (ν , µ ) we obtain
D − µ ( D −ν f (t )) = D − ( µ +ν ) f (t ) = D − (ν + µ ) f (t ) (2.33)
Equations (2.30) and (2.33) leads to
D − µ ( D −ν f (t )) = D −ν ( D − µ f (t )) = D − ( µ +ν ) f (t ) = D − (ν + µ ) f (t ) (2.34)
This proves the Theorem.
Theorem (1) can be also written in the form
J ν J µ f (t ) = J µ J ν f (t ) = J ν + µ f (t ) (2.35)
12
Chapter 3
Semi- integrals and Semi-derivatives
The most useful application of derivatives and integrals of noninteger order involve
the semiderivatives and semi-integrals (Oldham and Spanier 2002).
1
Substituting ν = in the definition of fractional integral given by Eq. (2.1a)
2
leads to the following expression of semi integral:
t t
−1 1
f (x )dx 1 f (t − x )dx
D 2 f (t ) =
π 0 t −x ∫ =
π ∫ x
(3.1)
0
1
substituting ν = we obtain the semi- derivative in the form:
2
t t
1
⎡ −1 ⎤ 1 d f (x )dx 1 d f (t − x )dx
D f (t ) = D ⎢ D 2 f (t ) ⎥ =
2
⎣ ⎦ π dt ∫ t −x
=
π dt ∫ x
(3.2)
0 0
Now, the semi-integrals and the semi-derivatives of some elementary functions are
deduced
1) The constant function : Using Equations (3.1) and (3.2) one obtains:
t
−1 1 Cdx t
D 2C =
π 0 x∫ = 2C
π
(3.3a)
1 t C
D 2C = D (2C )= (3.3b)
π πt
The following example illustrate the property
Now, using the definition (3.1) and Eq. (3.3a) and the substitution x = t sin 2 u , we
get
π
t 2
−1 −1 −1 t 1 t dx 4Ct
D 2 (D C ) = D
2 2 (2C
π
)=
π ∫ (2C )
π t −x
=
π 0 ∫
sin 2 udu = Ct
0
t
2C d x dx 2C d t π
∫
−1/ 2
D 1/ 2
(D C)= = ( ) =C
π dt 0
t −x π dt 2
t
−1 −1
∫
Note that: Cdx = Ct = D −1C = D 2 (D 2C ) .
0
−1
Example (3.2) : Evaluate D 2 t
Solution: Using the same substitution and the definition we get
t 3 π 3
−1 1 xdx 2t 2 2 4t 2
(t ) = ∫ = ∫ sin u du =
2 3
D
π 0
t −x π 0
3 π
1 −1
Let us verify the relation: D 2 (D 2 t ) = t ,(we use the substitution x = t sin 2 u )
3 3
1 −14t 2 − 1 4t 2 1
D ( D 2t ) = D (
2 ) = D [D 2 ( )] 2
3 π 3 π
3 π
t 2
1 d 4x dx 8 d 2 2
= ( ) = ∫
π dt 0 3 π t − x 3π dt
(t sin 4 udu ) = t ∫
0
0 0
m !! ⎪⎩ 2 m ∈ ` is even
1
Substituting ν = , λ = n in Eq. (2.4) ) we get:
2
n+1
−1 t 2 Γ (n + 1) 2 (2n )!! n + 12
D 2 (t ) =
n
= t
Γ (n + 32 ) π (2n + 1)!!
Using the following properties of double factorial:
14
e α (t −x ) e αt e −α x dx
t t
−1 1
∫ ∫
αt
D 2 (e ) = dx = ,
π 0 x π 0
x
−1 at
D 2 (at ) = erf ( t ln a ) (3.6)
π ln a
The semi- derivative of the exponential function can be obtained from (3.5) using the
definition (3.2):
1 1
D 2 (eα t ) = α eα t erf ( α t ) + (3.7)
πt
Where used the Leibniz’s formula
v (t )
d dv du
dt ∫ f (x )dx =f (v (t )).
dt
− f (u (t )).
dt
(3.8)
u (t )
15
−1 1 1
From Eqs. (3.3b) , (3.5) and (3.7) we get: D 2 (e αt ) = D 2 (e αt − 1) ,
α
4): The functions sint and cost :
t
−1 1 sin(t − x )dx 2
π ∫
D 2 (sin t ) = = [sin t C ( t ) − cos t S ( t )] (3.9)
0
x π
−1 2
D 2 (cos t ) = [cos t C ( t ) + sin t S ( t )] (3.10)
π
Where C (t ) and S (t ) are the Fresnel integrals defined by the relations
t t
∫
C (t ) = cos( y )dy , ∫
S (t ) = sin( y 2 )dy , and therefore, we have
2
0 0
t t
C( t)= ∫ cos( y S( t)= ∫ sin( y
2 2
)dy , )dy , (3.11)
0 0
The semi -derivatives can be obtained from the definition (3.2) using Leibniz’ formula
(3.8) as:
1 −1 d 2
D 2 (sin t ) = D {D 2 (sin t )} = { [sin t C ( t ) − cos t S ( t )]}
dt π
2 1
= [cos t C ( t ) + sin t S ( t )] + [sin t cos t − cos t sin t ] . Therefore,
π πt
1 2
D 2 (sin t ) = [cos t C ( t ) + sin t S ( t )] (3.12)
π
Taking into consideration Eq. (3.10) we get
1 −1
D 2 (sin t ) = D 2 (cos t ) (3.13)
Similarly, we get
1 1 −1
D 2 (cos t ) = −D 2 (sin t ) (3.14)
πt
Taking into consideration Eq. (3.3a) the preceding equation can be written in the
form:
−1 1
D 2 (sin t ) = D 2 (1 − cos t ) (3.15)
Chapter 4
Examples
(Semi- Integrals and Semi-Derivatives of Some Algebraic Functions)
f (x ) f (x )dx 11
t t
f (t − x )dx D
1/2
f ( x)
∫ ∫
−1/ 2
D f (x ) = =
π 0 t −x π 0
x = D[ D
−1/2
f ( x )]
1 x zero
1 1 dy
∫
( ) y = xz
x ⎯⎯⎯⎯
dy = xdz
→
π 0
y x −y
1
1
π ∫
−1/ 2 −1/ 2
= (1 − z ) z dz
0
1 1 1
= B( , )= π
π 2 2
π
2 x
( x) 1 x − y dy
∫
y = xz
⎯⎯⎯⎯
dy = xdz
→
π 0
y 2
x 3 1 x π x π
= B( , )= ( )=
π 2 2 π 2 2
3
1 1
x
dy y =(1+ x )sin θ ,
2 1
1+ x π
∫ 1+ x − y y
⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1+ x )sin θ cos θ d θ
→
(1 + x ) π x
0
−1
tan x
2 (1 + x ) sin θ cos θ d θ 2
∫
−1
= = tan ( x )
π (1 + x ) sin θ cos θ π
0
4
1+ x x
1 + x − y dy 1 tan −1 ( x )
1 y =(1+ x )sin 2 θ , +
π
∫ y
⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1+ x )sin θ cosθ d θ
→ πx π
0
x (1 + x ) −1
= + tan ( x )
π π
5 1
1
x
dy y =(1+ x )sin θ ,2 1− x
(1 + x )3/ 2
π
∫ (1 + x − y )
3
y
⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1+ x )sin θ cosθ d θ
→
(1 + x ) 2 π x
0
2 x
=
(1 + x ) π
17
6
1 1
x
dy y =(1− x )sinh θ 2 1
1− x π
∫ 1− x + y y
⎯⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1− x )sinh θ cosh θ d θ
→
(1 − x ) π x
0
2
= tanh −1 ( x )
π
7
1− x x 1
1 1 − x + y dy [
∫
y =(1− x )sinh 2 θ πx
⎯⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1− x )sinh θ cosh θ d θ
→
π y tanh −1( x )
0 − ]
π
x (1 − x )
+ tanh −1 ( x )
π π
8 1
1
x
dy 1+ x
∫
y =(1− x )sinh 2 θ
(1 − x )3/ 2 ⎯⎯⎯⎯⎯⎯⎯⎯⎯
dy = 2(1− x )sinh θ cosh θ d θ
→ (1 − x ) 2 π x
π 0 (1 − x + y )3 y
2 x
=
(1 − x ) π
9
1 x 1− x
1 dy y =(1− x ) tan 2 θ
(
1− x
)
π
∫ (1 − x + y ) y
⎯⎯⎯⎯⎯⎯⎯⎯→
dy = 2(1− x ) tan θ sec θ d θ
2
(1 − x )3/ 2 π x
x sin −1( x )
0 +
(1 − x )3/ 2 π x
2sin −1 ( x )
=
π (1 − x )
10
1 x
1+ x
1 dy y =(1+ x ) tanh θ 2
(
1+ x
)
∫
π (1 + x − y ) y
⎯⎯⎯⎯⎯⎯⎯⎯⎯ →
dy = 2(1+ x ) tanh θ sech θ d θ
2
(1 + x )
3/ 2
πx
0
−1
−1 x sinh ( x)
2sinh ( x ) −
= (1 + x )
3/ 2
πx
π (1 + x )
π
11 x
x 1 x − y dy y = x sin t 2
(1 + x ) π
∫ (1 + x − y ) y
⎯⎯⎯⎯⎯⎯→
dy = 2 x sin t cos tdt 2(1 + x )3/ 2
0
π
= π −
1+ x
π
12 1 x
1 dy 2
y = x sin t
x (1 + x )
π
∫ (1 + x − y ) x −y y
⎯⎯⎯⎯⎯⎯→
dy = 2 x sin t cos tdt
−
2(1 + x )3/ 2
0
18
π
=
1+ x
π
13 x
x 1 x − y dy
∫ (1 − x + y )
2
y = x sin t
⎯⎯⎯⎯⎯→
(1 − x ) π y dy = 2 x sin t cos tdt 2(1 − x )3/ 2
0
π
=− π +
1− x
π
14 1 x
1 dy
∫ (1 − x + y )
2
y = x sin t
x (1 − x )
⎯⎯⎯⎯⎯→
π x −y y dy = 2 x sin t cos tdt 2(1 − x )3/ 2
0
π
=
1− x
Chapter 5
Applications
The Tautochrone Curve
A tautochrone curve or isochrone curve is the curve for which the time taken by an object
sliding without friction in uniform gravity to its lowest point independent of its starting
point. Abel was interested in the tautochrone problem; that is, determining a curve in the
( x , y ) plane such that the time required for a particle to slide down the curve to its
lowest point is independent of its initial placement on the curve.
Firstly, we shall consider the time required for descent as a function of initial height.
Let us fix the lowest point of the curve at the origin and position the curve in the positive
quadrant of the plane, denoting by M ( x 0 , y 0 ) the initial point and P ( x , y ) any point
P )and then, S (0) = 0 . we also have the following conditions: at point M we have
t = 0, y = y 0 , v = 0 ( the initial velocity) and at point O we have
t = T ( y 0 ), y = 0, S = 0 . Assuming no frictional losses we may apply the
conservation of energy law (the sum of kinetic energy and potential energy is constant):
1 2 1
EM = mvM + mgy0 = E p = mvP2 + mgy . Since vM = 0 we get:
2 2
1 dS 2
m ( ) = mg ( y 0 − y ) (5.1)
2 dt
20
dS
Since the distance S is decreasing as the time increases we have < 0.
dt
dS dS dy
Therefore, Eq. (5.1) leads to =( ) = − 2 g ( y 0 − y ) . Thus, separating the
dt dy dt
variables one obtains
dS
()dy
dy
2 g dt = − (5.2)
(y 0 − y )
Integrating from t = 0, to t = T which corresponds from y = y 0 to y = 0 we get
T 0
(dS / dy )
∫
2 g dt = − ∫ (y 0 − y )
dy . Therefore,
0 y0
y0
(dS / dy )
2g T ( y 0 ) = ∫ (y 0 − y )
dy (5.3)
0
Equation (5.4) is the Abel’s integral equation. We shall use the fractional calculus to
obtain the solution of this equation (Samko et all 1993). Recalling the definition of the
y
1 f (z )
π ∫
−1/2
semi – integral: D f (y ) = dz we get
0
y −z
Therefore, we get
2g
S (y ) = D −1/2{T ( y )} (5.6)
π
Thus, we have obtained the solution of Abel’s integral equation in terms of the semi-
integral of T (y ) .
21
Now, to get the required curve we must set T ( y ) = T = Const . and use
y
D −1/2{C } = 2C and Eq. (5.6) becomes
π
y 2g
S ( y ) = 2T = 2 ay , a = 2 gT 2 / π 2 (5.7)
π π
Differentiating both sides with respect to y one obtains
dS ( y ) dx a
= 1 + ( )2 = , from which
dy dy y
dx 2 a dx a
1+ ( ) = → ( )2 = − 1 (5.8)
dy y dy y
Let
y = a sin 2 (θ / 2) . (5.9)
Then from (5.8) we get
dx dy
= cot(θ / 2) → = tan(θ / 2) (5.10)
dy dx
dy dθ
From (5.9) and (5.10) we get = a sin(θ / 2) cos(θ / 2) = tan(θ / 2) which leads to
dx dx
dx dx a
= a cos 2 (θ / 2) , and we get = (1 + cos θ )
dθ dθ 2
a
From the preceding equation we obtain x = (θ + sin θ ) + C . The curve is passing
2
through the origin so, x = 0 at y = 0 and therefore, C = 0 . Thus we obtain the
parametric equations of the tautochrone curve (a cycloid)
a a
x = (θ + sin θ ) y = (1 − cos θ ) (5.11)
2 2
AMNA ABDULSALAM YOUNIS AL-AMRY
22
References
[2] Gorenflo, R. and F. Mainardi (1997) , Fractional calculus : integral and differential
[3] Oldham Keith B. and Spanier Jerome.( 2002), The fractional Calculus, 2nd Ed,
[5] Samko S. G., Kilbas, A. A. and O. I. Marichev (1993), Fractional Integrals and